2020
DOI: 10.1182/blood.2020006941
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anticoagulation prior to COVID-19 infection: a propensity score–matched cohort study

Abstract: Tremblay and colleagues asked whether patients receiving either routine anticoagulation or antiplatelet therapy for existing conditions prior to becoming ill with COVID-19 have different outcomes from patients receiving neither therapy. After matching for existing comorbidities, this retrospective observational study finds no evidence for an effect of prediagnosis anticoagulation on mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
193
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(218 citation statements)
references
References 19 publications
16
193
3
1
Order By: Relevance
“…Given the strong procoagulant component that accompanies the pathophysiology of COVID-19, one hypothesis that has generated interest is whether being on anticoagulation for unrelated conditions prior to COVID-19 is protective for COVID-19 related outcomes. A recent propensity score-matched study compared 913 patients receiving anticoagulation (antiplatelet or anticoagulation therapy) with 2859 patients receiving neither at the time of COVID-19 diagnosis and found no statistically significant difference in survival, mechanical ventilation and need for hospital admission between both groups [25]. The uncertainty highlighted in observational studies and disagreement between guidelines re-iterates the importance of ongoing randomised trials such as COVID-HEP (NCT04345848) and REMAP-CAP [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the strong procoagulant component that accompanies the pathophysiology of COVID-19, one hypothesis that has generated interest is whether being on anticoagulation for unrelated conditions prior to COVID-19 is protective for COVID-19 related outcomes. A recent propensity score-matched study compared 913 patients receiving anticoagulation (antiplatelet or anticoagulation therapy) with 2859 patients receiving neither at the time of COVID-19 diagnosis and found no statistically significant difference in survival, mechanical ventilation and need for hospital admission between both groups [25]. The uncertainty highlighted in observational studies and disagreement between guidelines re-iterates the importance of ongoing randomised trials such as COVID-HEP (NCT04345848) and REMAP-CAP [26].…”
Section: Discussionmentioning
confidence: 99%
“…A higher proportion of patients with thrombotic complications died when compared with those without but this was not statistically significant (32 (39.5%) vs. 27 (25.5%), p = 0.059). Median (IQR) ICU length of stay was longer in patients who developed thrombotic complications 17 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) days vs. 12 (7-13) days, p = 0.003).…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, 8 studies were included in the final qualitative synthesis (Figure 1). [12][13][14][15][16][17][18][19][20] The main features of the 8 studies are presented in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…110,111 One study found no significant difference in outcomes, including mortality and mechanical ventilation; however, this study utilized a propensity-matched cohort, which limited the anticoagulation sample size to <150 patients and the authors do not clarify which anticoagulant was administered, if antiplatelets were given simultaneously, and there was no control for anticoagulation treatment regimen once admitted into the hospital. 110 The second study, also small with a patient population of 70, evaluated elderly patients with chronic heart disease that were on anticoagulants for at least 6 months prior to the diagnosis of COVID-19-related interstitial pneumonia and found that direct oral anticoagulants (DOACs), factor IIa and factor Xa inhibitors, appeared to be significantly protective. 111 Although this is an important study and a step in the right direction, the authors acknowledge that more thorough studies need to be performed.…”
Section: Factor Xa Inhibitors As a Potential Treatment For Covid-19mentioning
confidence: 96%